Response to Growth Hormone Treatment in a Patient with Insulin-Like Growth Factor 1 Receptor Deletion - Mahmoud, Ranim (J Clin Res Pediatr Endocrinol, 2017)
We report a six-year-old boy who presented with short stature, microcephaly, dysmorphic features, and developmental delay and who was identified with a terminal deletion of 15q26.2q26.3 containing the insulin-like growth factor receptor (IGF1R) gene in addition to a terminal duplication of the 4q35.1q35.2 region. We compare our case with other reports of deletions and mutations affecting the IGF1R gene associated with pre-and postnatal growth restriction. We report the dramatic response to growth hormone therapy in this patient which highlights the importance of identifying patients with IGF1R deletion and treating them early.